The Effect of Taxpayer Awareness, Tax Sanctions And Tax Knowledge On Individual Taxpayer Compliance In Tangerang City With Tax Socialization As A Moderation Variable - David Manuel; Jonnardi Jonnardi (PT. Publikasiku Academic Solution, 2023)
This study aims to examine the effect of taxpayer awareness, tax sanctions, and tax knowledge on individual taxpayer compliance in the city of Tangerang with tax socialization as a moderation variable. Distribution of Google form questionnaires (primary data) with subjects, namely individual taxpayers in the city of Tangerang, and processed using Smart PLS by testing data validity using convergent validity and data reliability using composite reability &; Cronbach Alpha. The results obtained from this study by bootstrapping method are that Taxpayer Awareness and Tax Knowledge have a significant influence on taxpayer compliance while Tax sanctions do not have a significant effect on taxpayer compliance. Meanwhile, tax socialization cannot moderate the effect of taxpayer awareness, tax sanctions, and tax knowledge on taxpayer compliance. Submission of research to be input and information regarding taxpayers' views on individual taxpayer compliance in Tangerang where the government can also continue to improve and develop for state development to be more adequate and support taxpayers in implementing their taxpayer compliance. It must also be effective and efficient so that taxpayers feel facilitated in carrying out their compliance